Average Error: 0.3 → 0.3
Time: 12.1s
Precision: 64
$\left(\left(-3\right) \cdot y + \left(2 \cdot x + t\right) \cdot x\right) \cdot x$
$x \cdot \left(\left(2 \cdot x + t\right) \cdot x - 3 \cdot y\right)$
\left(\left(-3\right) \cdot y + \left(2 \cdot x + t\right) \cdot x\right) \cdot x
x \cdot \left(\left(2 \cdot x + t\right) \cdot x - 3 \cdot y\right)
double f(double y, double x, double t) {
double r64576 = 3.0;
double r64577 = -r64576;
double r64578 = y;
double r64579 = r64577 * r64578;
double r64580 = 2.0;
double r64581 = x;
double r64582 = r64580 * r64581;
double r64583 = t;
double r64584 = r64582 + r64583;
double r64585 = r64584 * r64581;
double r64586 = r64579 + r64585;
double r64587 = r64586 * r64581;
return r64587;
}


double f(double y, double x, double t) {
double r64588 = x;
double r64589 = 2.0;
double r64590 = r64589 * r64588;
double r64591 = t;
double r64592 = r64590 + r64591;
double r64593 = r64592 * r64588;
double r64594 = 3.0;
double r64595 = y;
double r64596 = r64594 * r64595;
double r64597 = r64593 - r64596;
double r64598 = r64588 * r64597;
return r64598;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.3

$\left(\left(-3\right) \cdot y + \left(2 \cdot x + t\right) \cdot x\right) \cdot x$
2. Simplified0.3

$\leadsto \color{blue}{x \cdot \left(\left(2 \cdot x + t\right) \cdot x - 3 \cdot y\right)}$
3. Final simplification0.3

$\leadsto x \cdot \left(\left(2 \cdot x + t\right) \cdot x - 3 \cdot y\right)$

# Reproduce

herbie shell --seed 1
(FPCore (y x t)
:name "(- 3 * y + (2 * x + t) * x) * x"
:precision binary64
(* (+ (* (- 3) y) (* (+ (* 2 x) t) x)) x))